The Future of Liberal Democracy
XI, 288 p.
Keywords: Top scholars and practitioners from a variety of ideological perspectives consider liberal democracy and the Jeffersonian legacy, both in relation to key issues in the practice and theory of rights (human rights, individual rights) and in relation to key themes in political thought such as citizenship and participation that remain at the forefront of our debates about public life today. The first section of this collection provides historical and theoretical perspectives on Jefferson's ideals and thought. The second section explores the key themes of sovereignty, citizenship, participation, and accountability. A concluding section analyzes the relevance and place of Jefferson's legacy and the fate of liberal democracy in today's world. Contributors offer varying perspectives on questions such as: Is what is good for America good for the rest of the world? What are the constraints that exist on the global spread of democracy, liberal or otherwise?